Clinical Comparison of Outcomes of Early versus Delayed Carotid Artery Stenting for Symptomatic Cerebral Watershed Infarction due to Stenosis of the Proximal Internal Carotid Artery. (28th November 2016) - Liu, Huakun; Chu, Jianfeng; Zhang, Lei; Liu, Chaolai; Yan, Zhongrui; Zhou, Shengnian
Abstract : The aim of this study was to compare the clinical outcomes of early versus delayed carotid artery stenting (CAS) for symptomatic cerebral watershed infarction (sCWI) patients due to stenosis of the proximal internal carotid artery. We retrospectively collected clinical data of those who underwent early or delayed CAS from March 2011 to April 2014. The time of early CAS and delayed CAS was within a week of symptom onset and after four weeks from symptom onset. Clinical data such as second stroke, the National Institutes of Health Stroke Scale (NHISS) score, and modified Rankin Scale (mRS) score and periprocedural complications were collected. The rate of second stroke in early CAS group is lower when compared to that of delayed CAS group. There was no significant difference regarding periprocedural complications in both groups. There was a significant difference regarding mean NHISS score 90 days after CAS in two groups. Early CAS group had a significant better good outcome (mRS score ≤ 2) than delayed CAS group. We suggest early CAS for sCWI due to severe proximal internal carotid artery stenosis as it provides lower rate of second stroke, comparable periprocedural complications, and better functional outcomes compared to that of delayed CAS.